Electrogeneration of single nanobubbles at sub-50-nm-radius platinum nanodisk electrodes - Luo, Long (Langmuir : the ACS journal of surfaces and colloids, 2013)
The electrochemical generation of individual H(2) nanobubbles at Pt nanodisk electrodes immersed in a 0.5 M H(2)SO(4) solution is reported. A sudden drop in current associated with the transport-limited reduction of protons is observed in the i–V response at Pt nanodisk electrodes with radii of less than 50 nm. This decrease in current (~95% blockage) corresponds to the formation of a single H(2) nanobubble attached to the nanoelectrode that blocks proton transport to the surface. The current at which nanobubble formation occurs, i(nb)(p), is independent of scan rate and H(2)SO(4) concentration (for [H(2)SO(4)] > 0.1 M), indicating a critical concentration profile of electrogenerated H(2) required to nucleate a nanobubble. Finite element simulation based on Fick’s first law, combined with the Young–Laplace equation and Henry’s law, indicates that the concentration of H(2) near the nanoelectrode surface at i(nb)(p) exceeds the saturation concentration necessary to generate a nanobubble with a size comparable to the electrode size. The rapid dissolution of the nanobubble due to the high inner Laplace pressure is precisely balanced by the electrogeneration of H(2) at the partially exposed Pt surface, resulting in a dynamically stabilized nanobubble. Preliminary measurements of the i–t response during nanobubble formation indicate a two-step nucleation and growth mechanism with time scales on the order of 100 μs (or less) and ~1 ms, respectively